FRI0566-PC Prevalence of arterial hypertension in outpatients with rheumatoid arthritis. (23rd January 2014) - De La Vega, M. C.; Eraña, F.; Fecchio, C.; Villa, N.; Chiuzzi, E.; Uña, C.; Mata, D.; Russo, A.; Redondo, G.; Gamba, J.; Girard Bosch, M.; Villamil, A.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular mortality due to myocardial infarction, stroke and heart failure. Both, chronic inflammation leading to arterial stiffness, and some of the drugs used to treat RA, such as corticosteroids and leflunomide, are risk factors for developing arterial hypertension (HT). Objectives: The aim of this study is to determine the prevalence of HT in outpatients with RA at a rheumatology office in Buenos Aires, and describe their relationship with clinical, laboratory and disease activity Methods: We evaluated consecutive outpatients with a diagnosis of RA according ACR 90 criteria that attend to the Rheumatology office of a public hospital in Buenos Aires. Blood pressure (BP) was assessed by 3 protocolized measurements, clinical data was collected and disease activity was evaluated by DAS28-ESD. Statistical analysis was performed to establish prevalence of hypertension and to establish association with clinical and laboratory variables using Mann Whitney and Chi Square test. Significance was p≤0.05. Results: We analyzed 99 patients (85.9% female and 14.1% male) with a mean age of 51.3 years old (range 26-80). 79.8% had Functional Class I and II. The prevalence of hypertension in our population was 50.5%. The median time to progression of RA: 9.57 years, DAS 28: 4.06 (range: 1.54 to 7.55), 65.7% of individuals take corticosteroids. HT was associated with age (56.16 years (26-80) the HT patients versus 46.35 years (26-81) for non HT patients(p <0.0001). The abdominal diameter was greater for the HT group (95.74 cm (92.31- 99.17) versus 90.59 cm (86.67 - 94.51) (p=0.035). The other analyzed variables don´t show statistical significance Conclusions: Almost a half of RA patients had blood hypertension at the medical office during a standard control. It was significantly related to age and abdominal diameter. It was higher than the prevalence for the general population of Buenos Aires References: Solomon D, Karlson E, Rimm E, Cannuscio C, Mandl M. Cardiovascular morbidity and mortality in women diagnosed with Rheumatoid arthritis. Circulation 2003;107:1303–7. Ferrante D, Virgolini M. Encuesta Nacional de Factores de Riesgo 2005: resultados prinicpales. Prevalencia de factores de riesgo de enfermedades cardiovasculares en la Argentina. Rev. Argent Cardiol. 2007; 75; 20-29. Hernandez- Hernandez R, Silva H, Velasco M, et al. Hypertension in seven Latin American cities: the cardiovascular Risk Factor Multiple Evaluation in Latin America (CARMELA) study. J. Hypertens 2010; 28; 24-34. Panoulas V, et. al. Prevalence and associations of hypertension and its control in patients with rheumatoid arthritis. Rheumatology 2007;46:1477–1482 Disclosure of Interest: None Declared